TANGGUNG JAWAB HUKUM TERHADAP KONSUMEN PADA IKLAN PENGEMBANG PERUMAHAN BERDASARKAN UNDANG-UNDANG NOMOR 8 TAHUN 1999 TENTANG PERLINDUNGAN KONSUMEN - Tatawinarta, Barlian; Widiarty, Wiwik Sri; Betlehn , Andrew (Jurnal Cahaya Mandalika ISSN 2721-4796 (online), 2023)
The property sector is the backbone of development in Indonesia, thus property ownership greatly influences developers and impacts 174 other related industries and millions of Indonesian residents. The mismatch between housing advertisements and reality often disappoints consumers due to the breach of promises by housing developers. These breaches can include delays in construction, poor building quality, unfulfilled promised facilities, and even cases where developers misappropriate large sums of money from consumers. Such disparities between advertisements and reality have serious implications for consumer trust in existing developers. A satisfactory resolution to disputes, achieved through a win-win solution, is the desire and hope of all parties involved, as it brings numerous benefits and helps maintain harmonious relationships that have been established, or even allows for mutually beneficial future relationships. From a legal perspective, a just, beneficial, and legally certain dispute resolution is the hope and aspiration of all parties involved in the dispute. H.A. Mukti Arto, quoting Yahya Harahap, suggests that, in principle, the disputing parties seek a resolution that is fast, fair, and inexpensive, which serves as a general principle in dispute resolution.